(untitled) (Journal of Sciences & Technology, 2020)
This work aims to develop a new eco-composite construction that is good thermal insulation with a simple and inexpensive method. The prepared material is Portland cement and date palm fibers. This was characterized by: Raman spectroscopy to study the impact of fibers on the chemical behavior of the matrix, the hot wire method for measuring thermal conductivity and Scanning Electron Microscopy (SEM) for porosity measurement. The comparison of the results with those of Portland cement reveals that the inclusion of date palm fibers has no impact on the chemical behavior of the matrix and that the addition of these fibers increases the porosity and decreases the thermal conductivity cement.